The Role of private-owned enterprises in the defense industry according to the Omnibus Law - Dede Rusdiana (Journal of Economics and Business Letters, 2021)
The development of defense capabilities is a form of commitment to the state in creating a sense of security and peace. One of the concrete steps taken is the development of the defense industry. The basis for the development of the defense industry is the creation of a defense industry policy as stipulated in Law no. 16 of 2012 concerning the Defense Industry. The government also established the Defense Industry Policy Committee (KKIP) which is tasked with realizing the independence of the defense industry by bridging the needs of the military and the development of domestic strategic industries. Eight years ago, the government issued Law No. 16 of 2012 concerning the Defense Industry to support the master plan that had been established. However, now the Indonesian defense industry is still creating problems. It is clear in the law that only State-Owned Enterprises are the lead integrators, meaning that only SOEs have the right to produce the main components for defense equipment. In fact, if we learn from various countries such as America, Japan, China, and Korea, it can be seen that not only state-owned companies are capable of creating defense equipment, but private companies can also produce combat equipment.